2005
DOI: 10.1029/2004gb002445
|View full text |Cite
|
Sign up to set email alerts
|

Iron in the Sargasso Sea (Bermuda Atlantic Time‐series Study region) during summer: Eolian imprint, spatiotemporal variability, and ecological implications

Abstract: [1] We report iron measurements for water column and aerosol samples collected in the Sargasso Sea during July-August 2003 (summer 2003 and April-May 2004 (spring 2004. Our data reveal a large seasonal change in the dissolved iron (dFe) concentration of surface waters in the Bermuda Atlantic Time-series Study region, from $1-2 nM in summer 2003, when aerosol iron concentrations were high (mean 10 nmol m À3 ), to $0.1-0.2 nM in spring 2004, when aerosol iron concentrations were low (mean 0.64 nmol m À3 ). Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
178
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(201 citation statements)
references
References 75 publications
(113 reference statements)
21
178
2
Order By: Relevance
“…Consistent with our observations, Sedwick et al (2005) reported higher levels of iron in Sargasso Sea summer surface waters compared to the spring, presumably from eolian input from the Saharan desert. The periplasmic iron-binding transporter was one of only two periplasmic substratebinding proteins not observed in the metaproteomic data, the other being a protein of uncertain substrate specificity.…”
Section: Sargasso Sea Metaproteomicssupporting
confidence: 91%
“…Consistent with our observations, Sedwick et al (2005) reported higher levels of iron in Sargasso Sea summer surface waters compared to the spring, presumably from eolian input from the Saharan desert. The periplasmic iron-binding transporter was one of only two periplasmic substratebinding proteins not observed in the metaproteomic data, the other being a protein of uncertain substrate specificity.…”
Section: Sargasso Sea Metaproteomicssupporting
confidence: 91%
“…There is evidence based on the OMI Aerosol Index and MODIS observations that forest fires in Tasmania (Australia) may have led to a greater proportion of soluble Fe in aerosols sampled on the northeastern leg Guieu et al, 2005). It is possible that soluble iron deposition fluxes measured on the ship did not reflect Fe fluxes that fueled the observed NCP, and also that the fraction of bioavailable Fe was greater than that determined through the instantaneous leaching approach (Baker and Croot, 2010;Sedwick et al, 2005;Buck et al, 2006). A greater proportion of bioavailable iron, as parameterized in many atmospheric deposition models (e.g.…”
Section: Ncp Vs Aeolian Fe Deposition Estimatesmentioning
confidence: 99%
“…Light limitation in the lower euphotic zone would be expected to accelerate this process (Lomas and Lipschultz 2006). Indeed, work by Sedwick et al (2005) at several locations in the Sargasso Sea revealed that the lowest Fe concentration consistently occurred at or around the depth of PNM. While several studies have shown that some phytoplankton can substitute flavodoxin, which does not require Fe, for ferrodoxin under Fe-limiting conditions (La Roche et al 1995), the work of Milligan and Harrison (2000) has indicated that despite making flavodoxin, T. pseudonana also released nitrite under similar conditions.…”
mentioning
confidence: 99%